(untitled) (Scientific journal of the Fergana State University, 2024)
This article is focused on the issue of job creation and employment of traders. It is shown that commercial activity serves to fill the market with goods and satisfy the demand of the population. Information about the social status of traders, types of activities, and the gender and age structure of traders is provided. Also, analytical information on the issue of employment in markets covers unemployment, the level and structure of informal employment, including an analysis of determining the employment of the population through surveys.